Fatal staphylococcal scalded skin syndrome in a newborn. - Axelia, P.G.; Rani, S.A.D.; Reza, N.R.; Dewi, H.U.; Alkaff, F.F. (European Journal of Pediatric Dermatology, 2021)
Staphylococcal scalded skin syndrome (SSSS) is characterized by superficial blistering of the skin caused by exfoliative toxins of Staphylococcus aureus. SSSS predominantly affects children under five-year-old. We present a case of a 30-day-old female infant who developed circumscribed flaccid blisters within erythematous skin, with positive Nikolsky’s sign, without mucosal involvement. The ruptured blisters resulted in desquamation and scalded skin, then extending rapidly. The diagnosis of SSSS was achieved clinically and the patient was treated with intravenous cloxacillin. However, despite the given treatment in limited resources setting, the patient died due to sepsis. This case report highlights the difficulties in treating SSSS in limited-facilities hospital setting and underlines its life-threatening complications, such as sepsis. It is also aimed at raising awareness of SSSS as a possible differential diagnosis of superficial blistering and exfoliative skin disorders, especially in children population.